2014
DOI: 10.1371/journal.pone.0085653
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Novel NEFL mRNA Targeting microRNAs in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal disease characterized by progressive motor neuron degeneration and neurofilament aggregate formation. Spinal motor neurons in ALS also show a selective suppression in the levels of low molecular weight neurofilament (NEFL) mRNA. We have been interested in investigating the role of microRNAs (miRNAs) in NEFL transcript stability. MiRNAs are small, 20–25 nucleotide, non-coding RNAs that act as post-transcriptional gene regulators by targeting the 3′ untranslated reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Among the proteins related to cell growth and maintenance, nine are structural, nine are cytoskeletal, and two are from the extracellular matrix; among those related to energy metabolism, 17 are metabolic enzymes; and among those related to cell communication and signaling, six are adapter molecules (Table 2), which are essential for the pathways in which they are involved. The enzymes altered in energy metabolism are key molecules to regulate the energy metabolism pathway [21,22], and the structural and cytoskeleton proteins are indispensable to maintain cellular shape [23][24][25][26], in addition to playing a role in information transmission from dendrites to axons [27], a requirement for the cell to properly exercise its function. The receptor molecules at the membranes are related to cell communication, and, in the case of neurons, they are essential for a proper synaptic function [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Among the proteins related to cell growth and maintenance, nine are structural, nine are cytoskeletal, and two are from the extracellular matrix; among those related to energy metabolism, 17 are metabolic enzymes; and among those related to cell communication and signaling, six are adapter molecules (Table 2), which are essential for the pathways in which they are involved. The enzymes altered in energy metabolism are key molecules to regulate the energy metabolism pathway [21,22], and the structural and cytoskeleton proteins are indispensable to maintain cellular shape [23][24][25][26], in addition to playing a role in information transmission from dendrites to axons [27], a requirement for the cell to properly exercise its function. The receptor molecules at the membranes are related to cell communication, and, in the case of neurons, they are essential for a proper synaptic function [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the regulation of miRNAs in the central nervous system of ALS patients (19, 174) but information is limited in skeletal muscle. A recent study showed that miR-206 was dramatically up-regulated in skeletal muscle in a mouse model of ALS, while deficiency of miR-206 in this animal model accelerated the progression of the disease (47).…”
Section: Microrna In Skeletal Muscle Disorder and Atrophymentioning
confidence: 99%
“…As a latent tumour suppresser, NEFL has been testified to mediate cell growth and invasion in head and neck squamous cell carcinoma cells [33]. A crucial research uncovered that NEFL expression was specifically regulated by miR-b1336 and miR-b2403, which might be a direct target gene of the two miRNAs [34]. More interestingly, Peng et al discovered that miR-25 augmented cell proliferation and invasion in glioblastoma cells via immediately targeting NEFL [35].…”
Section: Discussionmentioning
confidence: 99%